1976
DOI: 10.1080/03014467600001731
|View full text |Cite
|
Sign up to set email alerts
|

The blood groups, serum groups, red-cell isoenzymes and haemoglobins of the Sandawe and Nyaturu of Tanzania

Abstract: Blood specimens from members of the click-speaking Sandawe tribe of Tanzania and of the adjacent Bantu-speaking Nyaturu tribe have been tested for antigens of 11 blood group systems, for variants of 3 plasma-protein systems and 9 red-cell-enzyme systems, for haemoglobin variants. The results are tabulated and gene frequencies computed. For most systems, the frequencies in the two tribes are similar to one another and, in so far as data are available, similar to the neighbouring Bantu-speaking tribes. The princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 5 publications
2
10
0
Order By: Relevance
“…El Hassan et al (1968) has reported a frequency of 0.4949 for Hp' among the Beja. However, a lower frequency of Hpl was observed in the random sample of the Sudanese from Khartoum (0.3580): Saha et al, 1978).The frequency of Hp' in the Sudanese tribes are lower than that of the other African countries, e.g., Nigeria (0.5977: Barnicot et al, 1960), Kenya (0.5682): Herzog et al, 1970), in Tanzania (0.6386 and 0.5686 in Sandawe and Nyaturu, respectively : Godber et al, 1976), and Uganda (0.65: Spitsyn et al, 1978). On the other hand a lower frequency of Hp' has also been reported in eastern Saudi Arabia (0.432: Goedde et al, 19791, tribes of western Saudi Arabia (0.3182-0.4167: Saha et al, 1980) and southern Arabia (0.4454: Marengo-Rowe et al, 1974).…”
Section: Serum Proteinsmentioning
confidence: 56%
See 4 more Smart Citations
“…El Hassan et al (1968) has reported a frequency of 0.4949 for Hp' among the Beja. However, a lower frequency of Hpl was observed in the random sample of the Sudanese from Khartoum (0.3580): Saha et al, 1978).The frequency of Hp' in the Sudanese tribes are lower than that of the other African countries, e.g., Nigeria (0.5977: Barnicot et al, 1960), Kenya (0.5682): Herzog et al, 1970), in Tanzania (0.6386 and 0.5686 in Sandawe and Nyaturu, respectively : Godber et al, 1976), and Uganda (0.65: Spitsyn et al, 1978). On the other hand a lower frequency of Hp' has also been reported in eastern Saudi Arabia (0.432: Goedde et al, 19791, tribes of western Saudi Arabia (0.3182-0.4167: Saha et al, 1980) and southern Arabia (0.4454: Marengo-Rowe et al, 1974).…”
Section: Serum Proteinsmentioning
confidence: 56%
“…Low frequencies of Hpo have also been reported in east (2.3%) and west Saudi Arabia (5%) and southern Arabia (9%) (Goedde et al, 1979;Saha et al, 1980;Marengo-Rowe et al, 1974). Hpo has also been reported to be present in a varying frequency in other African populations (Tanzania, 6.2%, Kenya, 4.0%) (Godber et al, 1976;Herzog et al, 1970). A moderate frequency of modified phenotypes such as 1-1 M, 2-1 M, 2-2 M were observed in both the Nuba and Hawazma tribes.…”
Section: Serum Proteinsmentioning
confidence: 80%
See 3 more Smart Citations